Pengaruh Dukungan emosional dan Toxic Relationship Terhadap psicologycal well being pada Mahasiswa - Zahroh, Elok Azimatuz; Mauludiyah, Lilik; Nuqul, Fathul Lubabin; Ridho, Ali; Muallifah, Muallifah (Universitas Medan Area, 2024)
This study aims to determine whether there is a relationship between social support and toxic relationships on the psychological well-being of students. The subjects of this study were students at the age of adolescents, namely vulnerable aged 19-25 years with male participants amounting to 24.3% and women amounting to 75.7% and the total respondents were 74. This research instrument, uses the scale of social support, the scale of toxic relationships, and the scale of psychological well-being. So that we found the results of the study that explained, that the calculation of each variable using Rstudio tools related to between variables and the results showed that the correlation between the variables of Psychology, well-being, and social support was -0.08 and was negative, which means that the two variables had a negative relationship. The correlation between toxic relationships and social support is 0.16, which means that both variables have a positive relationship. So it can be known that the psychology of well-being and social support have no relationship while toxic relationships and social support are relationships experienced by late adolescents